Pérégrinations entre sciences du langage et didactique des langues - Élodie Oursel (Recherches en didactique des langues et des cultures)
This article delivers the testimony of a young researcher in language didactics whose work resembles many others in applied linguistics. However, in France, the belonging of this work to the latter research field has been denied several times. This testimony is emblematic of the path of some researchers in language didactics in France, who have had to forget, hide, or even deny their relations with applied linguistics, due to the historical positioning of language didactics. But it also is the testimony of a young researcher: she hasn’t lived the historical debates from the inside, so she sees the situation with a fresh eye. How is her work related to didactics? to applied linguistics? What became of the latter field in the French scientific landscape? What questions can we raise today to help it regain its legitimate place next to language didactics?